Biliteracy at University for Future Translators: Perceptions and Correlations; [Biliteracidad en la Universidad Para Futuros Traductores: Percepciones y Correlaciones] - Singer-Contreras, N; Dos Santos-Marques, A (Universidad de la Serena,Departamento de Artes y Letras, 2023)
This research aims to describe lecturers’ and students’ perceptions about the development of their academic writing in language learning in the context of an undergraduate Spanish-English-Portuguese translation programme. The concept of biliteracy (Hornberger, 1990; 2003; 2013) is compared to the features identified by the participants’ experiences in the writing of academic genres in their first language (L1), Spanish, and in their second languages (SL), Portuguese and English. Data are examined in terms of writing content, means and contexts that are required to produce meanings in those languages at university level. The methodological design involves a longitudinal case study. For this paper, data obtained from a first semi-structured interview round were gathered. These were classified in two categories: writing contexts and mastery of genres required in their programmes. Results reveal that students move along English-Spanish-Portuguese biliteracy contexts according to the specific purposes of writing tasks. They appear to struggle with achieve the required academic register and relate their experiences with the languages they study. Lecturers, on the other hand, writing practice is approached from mostly monolingual course units. These results highlight the linguistic and pedagogical implications concerning the collective and personal development of academic writing in SL, English and Portuguese, as well as the participants’ L1, Spanish. © 2023 U.S. Fish and Wildlife Service. All rights reserved.